Outcomes in intraductal papillary mucinous neoplasm-derived pancreatic cancer differ from PanIN-derived pancreatic cancer - Habib, Joseph; Rompen, Ingmar F.; Javed, Ammar A.; Grewal, Mahip; Kinny-Köster, Benedict; Andel, Paul C.M.; Hewitt, D. Brock; Sacks, Greg D.; Besselink, Marc G.; van Santvoort, Hjalmar C.; Daamen, Lois A.; Loos, Martin; et al. (Journal of gastroenterology and hepatology, 2024)
Background and Aim Intraductal papillary mucinous neoplasm (IPMN)-derived pancreatic ductal adenocarcinoma (PDAC) management is generally extrapolated from pancreatic intraepithelial neoplasia (PanIN)-derived PDAC guidelines. However, these are biologically divergent, and heterogeneity further exists between tubular and colloid subtypes. Methods Consecutive upfront surgery patients with PanIN-derived and IPMN-derived PDAC were retrospectively identified from international centers (2000-2019). One-to-one propensity score matching for clinicopathologic factors generated three cohorts: IPMN-derived versus PanIN-derived PDAC, tubular IPMN-derived versus PanIN-derived PDAC, and tubular versus colloid IPMN-derived PDAC. Overall survival (OS) was compared using Kaplan-Meier and log-rank tests. Multivariable Cox regression determined corresponding hazard ratios (HR) and 95% confidence intervals (95% CI). Results The median OS (mOS) in 2350 PanIN-derived and 700 IPMN-derived PDAC patients was 23.0 and 43.1 months (P < 0.001), respectively. PanIN-derived PDAC had worse T-stage, CA19-9, grade, and nodal status. Tubular subtype had worse T-stage, CA19-9, grade, nodal status, and R1 margins, with a mOS of 33.7 versus 94.1 months (P < 0.001) in colloid. Matched (n = 495), PanIN-derived and IPMN-derived PDAC had mOSs of 30.6 and 42.8 months (P < 0.001), respectively. In matched (n = 341) PanIN-derived and tubular IPMN-derived PDAC, mOS remained poorer (27.7 vs 37.4, P < 0.001). Matched tubular and colloid cancers (n = 112) had similar OS (P = 0.55). On multivariable Cox regression, PanIN-derived PDAC was associated with worse OS than IPMN-derived (HR: 1.66, 95% CI: 1.44-1.90) and tubular IPMN-derived (HR: 1.53, 95% CI: 1.32-1.77) PDAC. Colloid and tubular subtype was not associated with OS (P = 0.16). Conclusions PanIN-derived PDAC has worse survival than IPMN-derived PDAC supporting distinct outcomes. Although more indolent, colloid IPMN-derived PDAC has similar survival to tubular after risk adjustment.
Gesehen am 14.02.2025
Erstveröffentlichung: 31. Juli 2024